The Role of the Gut Microbiome in Exercise Physiology and Athletic Performance: A Review of Evidence - Pustuła, Paweł; Michnowska, Wiktoria; Hebda, Patryk; Czapliński, Mieszko; Bruska, Natalia; Błaszkowski, Bartłomiej; Bilyk, Andrii; Wolski, Adam; Kubicki, Mateusz; Więckowska, Katarzyna (Quality in Sport, 2026)
Background The human gut microbiome interacts with host metabolism, immunity, and neuroendocrine signaling. Evidence shows habitual exercise modulates microbial diversity and function, with athletes exhibiting distinct "athletic" profiles enriched in short-chain fatty acid (SCFA)–producing taxa and altered metabolism versus sedentary people. Aim Synthesize evidence on the bidirectional gut microbiome–exercise relationship, focusing on microbial links to exercise physiology, training adaptations, performance, and microbiome-targeted strategies for athlete health/performance. Material and methods Comprehensive review of Google Scholar, Scopus, PubMed for human/animal studies on: (1) exercise-induced microbiota changes; (2) microbiome–fitness/performance associations; (3) microbial metabolites (e.g., SCFAs, bile acids); (4) dietary/probiotic/prebiotic interventions in athletes/active individuals. Prioritized recent reviews, RCTs, longitudinal studies; no meta-analysis due to heterogeneity. Results Endurance exercise links to higher diversity, SCFA-producers, and carbohydrate/amino acid metabolism capacity; extreme training causes dysbiosis, permeability, inflammation. SCFAs mediate diet–microbiota–host effects on mitochondria, substrate use, insulin sensitivity; gut signals affect immunity, barrier, gut–brain axis. Fiber-rich diets, select probiotics/synbiotics reduce illness, GI issues, inflammation, and may boost endurance/recovery. Conclusions The gut microbiome represents a modifiable factor in exercise physiology and athletic performance. Well-periodized training combined with microbiome-supportive nutrition may promote metabolic efficiency, immune resilience, and psychological robustness, whereas chronic excessive training and suboptimal diets may have adverse effects. Further progress requires well-designed, sport- and sex-specific longitudinal studies integrating multi-omics approaches and standardized exercise and intervention protocols.